Tissue chemistry of Babylonia spirata (Linnaeus) - Shanmugam, A; Bhuvaneswari, T; Arumugam, M; Nazeer, R A; Sambasivam, S (Indian Journal of Fisheries, 2011)
Biochemical composition of different body parts of Babylonia spirata(L) invarious size groups was studied.Â Among the body parts, gonad and digestivegland showed highest biochemical composition and acts as a storage sitefollowed by foot and exhibitedÂ a distinct seasonal cycle. The size groups of 40â€“ 45 mm andÂ 45 â€“ 50 mm animals showed higher values of biochemicalcomponents.Â Maximum protein value of 69.09 % was recorded in May 1998 inthe size group of 50 â€“ 55 mm and the highest carbohydrate value of 9.20 % wasrecorded in the 50 â€“55mm size group.Â The maximum lipid value of 9.5 % wasrecorded in the 50 â€“55mm size groups animals.